Mitochondrial Chaperones and Proteases in Cardiomyocytes and Heart Failure - Chen, Zee; Huang, Lei; Tso, Alexandria; Wang, Shijia; Fang, Xi; Ouyang, Kunfu; Han, Zhen (Frontiers in Molecular Biosciences, 2021)
Heart failure is one of the leading causes of morbidity and mortality worldwide. In cardiomyocytes, mitochondria are not only essential organelles providing over 90% of the ATP necessary for contraction, but they also play critical roles in regulating intracellular Ca2+ signaling, lipid metabolism, production of reactive oxygen species (ROS), and apoptosis. Since mitochondrial DNA only encodes 13 proteins, most mitochondrial proteins are nuclear DNA-encoded, synthesized and transported from the cytoplasm, refolded in the matrix to function alone or as a part of a complex, and degraded if damaged or incorrectly folded. Mitochondria possess a set of endogenous chaperones and proteases to maintain mitochondrial protein homeostasis. Perturbation of mitochondrial protein homeostasis usually precedes disruption of the whole mitochondrial quality control system, and has been recognized as one of the hallmarks of cardiomyocyte dysfunction and death. In this review, we focus on mitochondrial chaperones and proteases, and summarize recent advances in understanding how these proteins are involved in the initiation and progression of heart failure.